2010
DOI: 10.3109/08880011003749678
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcoma of the Tongue: Report of a Case and Review of the Literature

Abstract: Rhabdomyosarcomas are the most common soft tissue tumors in children. Head and neck is one of the most frequently affected site. Within the nonparameningeal, nonorbital head and neck region, rhabdomyosarcomas of the tongue are very rare. We present a 2-year-old boy diagnosed with rhabdomyosarcoma of the tongue. The child was treated with complete surgical resection and chemotherapy. He is followed up with no evidence of disease 6 months after termination of therapy. The literature on rhabdomyosarcoma of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…In the Intergroup Rhabdomyosarcoma Studies(IRS) I, II and III, only 7 rhabdomyosarcomas of the tongue were registered, representing 0.34% of IRS participants [10] . Rejin Kebudi et al summarized a total of 13 cases of lingual RMS reported in English literatures from 1973 to 2009, whose median age was 3.5 months, much younger than the median age of 5 years in children with RMS reported in literature [9] . Our 2 cases were initially considered as mucoceles and tongue root tumors of unknown nature in local hospital respectively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the Intergroup Rhabdomyosarcoma Studies(IRS) I, II and III, only 7 rhabdomyosarcomas of the tongue were registered, representing 0.34% of IRS participants [10] . Rejin Kebudi et al summarized a total of 13 cases of lingual RMS reported in English literatures from 1973 to 2009, whose median age was 3.5 months, much younger than the median age of 5 years in children with RMS reported in literature [9] . Our 2 cases were initially considered as mucoceles and tongue root tumors of unknown nature in local hospital respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In case 2, tongue mass was found because of the symptom of choking milk. The differential diagnosis of the mass of tongue includes hemangiomas, fibroma, rhabdomyoma, lymphangioma, and lingual thyroid [8,9] , and primary lingual RMS is rare, the definite diagnosis of which requires pathological examination. In the Intergroup Rhabdomyosarcoma Studies(IRS) I, II and III, only 7 rhabdomyosarcomas of the tongue were registered, representing 0.34% of IRS participants [10] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although malignant tumors, such as lymphoma and rhabdomyosarcoma, were considered, these are exceedingly rare in this location. 4 Benign tumors, such as teratoma and epulis, are more likely in this location and can present as rapidly growing tongue lesions, but these entities are also rare. 5,6 Although, grossly, the lesion appeared to be neoplastic, a thorough evaluation with multiple tumorspecific stains did not demonstrate a neoplastic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Rhabdomyosarcoma (RMS) comprises a group of soft tissue neoplasms that shares the propensity to undergo myogenesis. 1 There is a bimodal distribution of presentation with an initial peak incidence between 2-5 years of age and a second surge at [10][11][12][13][14][15][16][17][18][19]…”
Section: Introductionmentioning
confidence: 99%